Effects of Zinc Source and Enzyme Addition on the Fecal Microbiota of Dogs - Pereira, Ana Margarida; Maia, Margarida R. G.; Pinna, Carlo; Biagi, Giacomo; Matos, Elisabete; Segundo, Marcela A.; Fonseca, António J. M.; Cabrita, Ana R. J. (Frontiers in Microbiology, 2021)
Supplemental zinc from organic sources has been suggested to be more bioavailable than inorganic ones for dog foods. However, the bioavailability of zinc might be affected by dietary constituents such as phytates. The present study aimed to evaluate the effects of two zinc sources (zinc sulfate and zinc proteinate) and the addition of a multi-enzymatic complex from the solid-state fermentation of Aspergillus niger on end-products of fecal fermentation and fecal microbiota of adult Beagles fed a high-phytate diet. The experimental design consisted of three 4 × 4 Latin Squares with a 2 × 2 factorial arrangement of treatments (n = 12 Beagles), with four periods and four diets: zinc sulfate without (IZ) or with (IZ +) enzyme addition, and zinc proteinate without (OZ) or with (OZ +) enzyme addition. Enzyme addition significantly affected Faith’s phylogenetic diversity index, whereas zinc source did not affect either beta or alpha diversity measures. Linear discriminant analysis effect size detected nine taxa as markers for organic zinc, 18 for inorganic source, and none for enzyme addition. However, with the use of a negative binomial generalized linear model, further effects were observed. Organic zinc was associated with a significantly higher abundance of Firmicutes and lower Proteobacteria and Bacteroidetes, although at a genus level, the response varied. The DNA abundance of Clostridium cluster I, Clostridium cluster XIV, Campylobacter spp., Ruminococcaceae, Turicibacter, and Blautia was significantly higher in dogs fed IZ and IZ + diets. Higher abundance of genus Lactobacillus was observed in dogs fed enzyme-supplemented diets. End-products of fecal fermentation were not affected by zinc source or enzymes. An increase in some taxa of the phyla Actinobacteria and Firmicutes was observed in feces of dogs fed organic zinc with enzyme addition but not with inorganic zinc. This study fills a gap in knowledge regarding the effect of zinc source and enzyme addition on the fecal microbiota of dogs. An association of zinc bioavailability and bacteria abundance is suggested, but the implications for the host (dog) are not clear. Further studies are required to unveil the effects of the interaction between zinc sources and enzyme addition on the fecal microbial community.